Vagus nerve stimulation for pharmacoresistant epilepsy secondary to encephalomalacia: A single-center retrospective study - Guo, Mengyi; Wang, Jing; Xiong, Zhonghua; Deng, Jiahui; Zhang, Jing; Tang, Chongyang; Kong, Xiangru; Wang, Xiongfei; Guan, Yuguang; Zhou, Jian; Zhai, Feng; Luan, Guoming; et al. (Frontiers in Neurology, 2023)
Objective Vagus nerve stimulation (VNS) is an adjunctive treatment for pharmacoresistant epilepsy. Encephalomalacia is one of the most common MRI findings in the preoperative evaluation of patients with pharmacoresistant epilepsy. This is the first study that aimed to determine the effectiveness of VNS for pharmacoresistant epilepsy secondary to encephalomalacia and evaluate the potential predictors of VNS effectiveness. Methods We retrospectively analyzed the seizure outcomes of VNS with at least 1 year of follow-up in all patients with pharmacoresistant epilepsy secondary to encephalomalacia. Based on the effectiveness of VNS (≥50% or <50% reduction in seizure frequency), patients were divided into two subgroups: responders and non-responders. Preoperative data were analyzed to screen for potential predictors of VNS effectiveness. Results A total of 93 patients with epilepsy secondary to encephalomalacia who underwent VNS therapy were recruited. Responders were found in 64.5% of patients, and 16.1% of patients achieved seizure freedom at the last follow-up. In addition, the responder rate increased over time, with 36.6, 50.5, 64.5, and 65.4% at the 3-, 6-, 12-, and 24-month follow-ups, respectively. After multivariate analysis, seizure onset in adults (>18 years old) (OR: 0.236, 95%CI: 0.059–0.949) was found to be a positive predictor, and the bilateral interictal epileptic discharges (IEDs) (OR: 3.397, 95%CI: 1.148–10.054) and the bilateral encephalomalacia on MRI (OR: 3.193, 95%CI: 1.217–8.381) were found to be negative predictors of VNS effectiveness. Conclusion The results demonstrated the effectiveness and safety of VNS therapy in patients with pharmacoresistant epilepsy secondary to encephalomalacia. Patients with seizure onset in adults (>18 years old), unilateral IEDs, or unilateral encephalomalacia on MRI were found to have better seizure outcomes after VNS therapy.